Generation Z Consumers as a Challenge for a Community Manager - Olga Lawinska; Anna Korombel (International Journal of Supply Chain Management, 2019)
Social media - especially for young generation Z - have become an essential tool for establishing private, professional and consumer relations. People from generation Z constitute an increasingly demanding group of customers. They do not know the era when the Internet or smartphones have not existed. In fact, they have been using these technologies from their earliest years, hence they are often called digital natives. The possibility of using social media commercially for marketing purposes gave rise to a new profession - community manager. It refers to a professional who deals with day-to-day communication with fans and interacts with the recipients of published content. He or she answers questions from fans, responds to emails, and often conducts long discussions to keep fans engaged, strengthen the brand's contact with its potential customers and build a positive image of the company. The aim of this paper is to identify challenges/tasks for community managers resulting from special characteristics of generation Z members and their behaviour on social media. As well as literature review, a survey was conducted among 233 students - representatives of generation Z. Analysis of the gathered empirical data gave basis for verifying the formulated research hypotheses and concluding that people from generation Z are not loyal customers, meaning that they usually do not get attached to the brand/company, product/service, and that generation Z customers are not willing to defend a company's reputation on social media. Additionally, the strength of relationships between the analysed variables and a respondent's sex and place of residence was verified.